222Rn Determination in Water and Brine Samples Us-ing Liquid Scintillation Spectrometry (Brazilian Journal of Radiation Sciences, 2019)
Liquid scintillation spectrometry (LSC) is the most common technique used for 222Rn determination in environmental aqueous sample. In this study, the performance of water-miscible (Ultima Gold AB) and immiscible (Optiscint) liquid scintillation cocktails has been compared for different matrices. 241Am, 90Sr and 226Ra standard solutions were used for LSC calibration. 214Po region was defined as better for both cocktails. Counting efficiency of 76 % and optimum PSA level of 95 for Ultima Gold AB cocktail, and counting efficiency of 82 % and optimum PSA level of 85 for Optiscint cocktail were obtained. Both cocktails showed similar results when applied for 222Rn activity determination in water and brine samples. However the Optiscint is recommended due to its quenching resistance. Limit of detection of 0.08 and 0.06 Bq l−1 were obtained for water samples using a sample:cocktail ratio of 10:12 mL for Ultima Gold AB and Optiscint cocktails, respectively. Limit of detection of 0.08 and 0.04 Bq l−1 were obtained for brine samples using a sample:cocktail ratio of 8:12 mL for Ultima Gold AB and Optiscint cocktails, respectively.